PhD proposal (Gregynog 2010): short selling and stock returns - Mohamad, Azhar (2010)
Finance theory in asset pricing chapter has long made strong assumptions on short selling. In CAPM for example, lending and borrowing of securities is assumed to be unlimited and therefore short selling is assumed in place without cost and without restrictions. In real world, this is not the case. In restricting or prohibiting short selling, financial markets actually depart from asset pricing assumptions. Short selling around the world has a colourful history; Hong Kong bans short selling in 1990 while Malaysia bans short selling in 1998 but uplifts the ban in 2007. Wall Street and UK both ban short selling on 19 September 2008 with Wall Street uplifts the ban one month later while UK follow suit four months later. While Wall Street adopts up-tick rule to prevent short sellers from depressing the stock price, UK opts for disclosure regime to enhance transparency to avoid abusive short selling. It will be interesting to investigate the informational content of short selling, its relationship with stock returns and to examine the effect of short selling ban on stock returns. Most studies on informational role of short selling center on the US markets and they find the higher is the short interest the more negative is the stock abnormal returns. These findings basically suggest high short interest is a bearish signal and in the linguistic of Efficient Market Hypothesis (EMH), they infer securities market is somewhat not even weak efficient because past securities market data can be used to predict securities’ returns. So the study of informational role of short interest in the UK stock market will be very interesting as it will provide evidence against or for EMH.